2004
DOI: 10.1097/00005537-200409000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Findings in Users of Combination Corticosteroid and Bronchodilator Therapy

Abstract: Dysphonia caused by a change in the surface mucosa is a side effect from the use of DPI therapy for asthma. The high-impact force during inhalation of the medication and carrier leads to deposition of particles in the upper airway. We believe the extent of mucosal irritation can be minimized by patient education in the proper delivery of DPI. In some cases, however, return of the two medications delivered separately was necessary. The irritation of the laryngeal mucosa and return of normal vibratory parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 12 publications
2
49
0
6
Order By: Relevance
“…The meta-analysis of randomized controlled trials by Rachelefsky et al 14 found that ICS MDI devices were associated with a 5-fold greater risk of dysphonia when compared with placebo MDI devices, whereas the ICS DPI devices had a 3-fold greater risk vs placebo DPI devices. Insofar as dysphonia in patients receiving combined corticosteroid and bronchodilator therapy, Mirza et al 24 described voice and laryngeal changes in 5 patients who switched from corticosteroid and bronchodilator therapy administered separately to concurrent administration. Most patients had areas of hyperemia and a plaque pattern on the surface mucosa.…”
Section: Dosage and Delivery Of Icsmentioning
confidence: 99%
“…The meta-analysis of randomized controlled trials by Rachelefsky et al 14 found that ICS MDI devices were associated with a 5-fold greater risk of dysphonia when compared with placebo MDI devices, whereas the ICS DPI devices had a 3-fold greater risk vs placebo DPI devices. Insofar as dysphonia in patients receiving combined corticosteroid and bronchodilator therapy, Mirza et al 24 described voice and laryngeal changes in 5 patients who switched from corticosteroid and bronchodilator therapy administered separately to concurrent administration. Most patients had areas of hyperemia and a plaque pattern on the surface mucosa.…”
Section: Dosage and Delivery Of Icsmentioning
confidence: 99%
“…Dysphonia has been explained on the presence of thyroarytenoid myopathy, laryngeal candidiasis and or steroid induced laryngitis. Common laryngeal stroboscopic findings include bowing of the vocal folds, presence of glottal gap, vocal fold irregularities, and presence of vascular lesions, mucosal thickening and leukoplakia [25]. Other findings include abnormal closure patterns, phase and amplitude asymmetry, and or the presence of exudates like material on the vocal folds.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] The physiological mechanisms underlying vocal decrement have been attributed in part to muscular changes including laryngeal myopathy and vocal fold bowing. However, recent research suggests that local mucosal changes resulting from exposure to inhaled corticosteroids and/or LABAs are most likely to induce dysphonia in the majority of speakers with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Inhaled therapies are believed to induce dysphonia, throat dryness, vocal fatigue, and discomfort. [4][5][6][7][8][9][10] Gallivan and colleagues 11 reported dysphonia in more than 80% of speakers that were prescribed inhaled medications. As voice quality depends on the structural and functional integrity of vocal fold mucosa, changes to mucosal appearance in individuals receiving inhaled therapies have been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation